Network of nicotinamide mononucleotide biosynthesis: substrate tracking, rate-limiting enzyme, and regulatory strategy - Puyue Zhang; Ziru Ye; Zhong Tian; Qing Liu; Yong Huang (Synthetic and Systems Biotechnology)
Nicotinamide mononucleotide (NMN) is a nucleotide of significant biological importance, found abundantly in various foods such as meat, fruits, and vegetables. Recently, its potential effects in delaying aging have attracted considerable attention. Although chemical synthesis methods are commonly employed, they do not align with green production standards. In contrast, the biosynthesis of NMN is both safer and more environmentally sustainable. In this review, we established a novel “substrate-pathway-enzymology” framework to analyze the research on NMN biosynthesis. First, we systematically trace four substrates (nicotinamide ribose, nicotinamide, niacin, and nicotinamide adenine dinucleotide) and their respective metabolic routes. Then, we thoroughly investigate key enzymes through structural biology and protein engineering approaches, and converge the fragmented research findings across pathways to construct a comprehensive NMN biosynthesis network, revealing intricate metabolic regulations and pathway interactions. Through comparative analysis, the most promising biosynthetic pathway and prospects are discussed. Additionally, this review also provides original perspectives for NMN industrial development.